PERAN PEMERINTAH DAERAH DALAM PENGELOLAAN TEMPAT PELELANGAN IKAN DI KABUPATEN JEPARA - Sandi Hertanto; Kushandajani Nur .; Puji Astuti (Journal of Politic and Government Studies, 2013)
Fish Auction is one of the most important things in fisheries sector for fishermen to drop their ships and sell their fish. The problem that often occurred is fishermen are inclined to sell and put their fishes in auction outside the legal auction place. This condition caused by the management of the auction place itself that is still unstructured, minimum humanresources in managing the auction place, the facilities provided and also the low level of security compare to outside the legal auction place.Objective of this research is to know how the roles of the local government (Department of Oceanography and Fisheries) in managing fish auction place, along with the obstacle factors in managing the place in Jepara regency.To reveal the problems from the objectives, the researcher used the qualitative method with the analysis descriptive approach, in which the efforts of this research is to describe the condition in the present time in one research object by using the theory of management function by George Terry as the basis ground in conducting this research. So that the division of this research consists of planning, organizing, conducting, and controlling that are done by the local government.The result of this research showed that the roles of the local government in managing the fish auction place in Jepara regency could not be said as optimal because there are several obstacles and problems, so that particular controls are still needed from the local government to minimalist those conditions. Advice given the increase quality and quantity of the human resources, to evaluate the performnceof employees involved in the management of fish auction, and also increase the support in society in every level.Key words : government’s roles, management, fish auction place.